Maternal Knowledge, Attitudes, and Practices of Exclusive Breastfeeding: A Cross-Sectional Study in the Primary Health Care Centers of Gusau, Nigeria (2025) - Muhammad Abubakar Nuhu; Abdulhamid Umar Abdulkadir; Hussaini Yakubu Anka (Journal of Human Lactation, 2026)
Background: This study assessed the knowledge, attitudes, and practices (KAPs) of exclusive breastfeeding (EBF) among mothers visiting Shagari, Kwata, and Dr. Karima Primary Health Care in Gusau, Nigeria. EBF, defined as providing only breast milk for the first 6 months, is not universally practiced in Nigeria, particularly in rural areas. This research aimed to identify the factors influencing mothers' decisions to adopt EBF. Methods: A facility-based cross-sectional study was conducted in 2025 at three primary healthcare centers. Using systematic random sampling, 400 breastfeeding mothers aged 18–41 years were selected to complete a semistructured questionnaire. The data were analyzed via logistic regression to determine associations. Results: The results revealed a high prevalence of EBF, with 77.8% of mothers practicing it. The key factors significantly associated with a greater likelihood of EBF practices included having knowledge of EBF (AOR = 3.85, p = 0.001), receiving EBF training (AOR = 7.343, p < 0.001), and obtaining community support (AOR = 12.22, p < 0.001). Other influential factors included having a secondary education and a positive attitude toward EBF. Conclusion: This study revealed that most mothers demonstrated good knowledge, positive attitudes, and strong practices regarding EBF. To sustain and improve these outcomes, the findings suggest increased investment in educating mothers about the benefits of EBF during and after pregnancy. This enables informed decision-making, ultimately benefiting both maternal and child health.